1998
DOI: 10.1128/jb.180.13.3345-3352.1998
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the SOS Response Increases the Efficiency of Global Nucleotide Excision Repair of Cyclobutane Pyrimidine Dimers, but Not 6-4 Photoproducts, in UV-Irradiated Escherichia coli

Abstract: Nucleotide excision repair (NER) is responsible for the removal of a variety of lesions from damaged DNA and proceeds through two subpathways, global repair and transcription-coupled repair. InEscherichia coli, both subpathways require UvrA and UvrB, which are induced following DNA damage as part of the SOS response. We found that elimination of the SOS response either genetically or by treatment with the transcription inhibitor rifampin reduced the efficiency of global repair of the major UV-induced lesion, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 46 publications
3
45
3
Order By: Relevance
“…1B). As well, in accordance with previous publications (43,44), in all age groups (6 -4) PPs were removed faster than thymine dimers (PϽ0.005, ANOVA post hoc analysis by Fisher and Bonferroni/ Dunn). There was no statistically significant difference in the slope (rate of removal) of (6 -4)PPs early (up to 3 h) vs. late (from 3 h on) when all the donors were tested together (Pϭ0.24) or when each age group was tested alone.…”
Section: Removal Rate For Thymine Dimers and (6 -4) Pps Decreases In supporting
confidence: 89%
See 1 more Smart Citation
“…1B). As well, in accordance with previous publications (43,44), in all age groups (6 -4) PPs were removed faster than thymine dimers (PϽ0.005, ANOVA post hoc analysis by Fisher and Bonferroni/ Dunn). There was no statistically significant difference in the slope (rate of removal) of (6 -4)PPs early (up to 3 h) vs. late (from 3 h on) when all the donors were tested together (Pϭ0.24) or when each age group was tested alone.…”
Section: Removal Rate For Thymine Dimers and (6 -4) Pps Decreases In supporting
confidence: 89%
“…Because UV irradiation can induce NER proteins in prokaryotic (44) as well as in eukaryotic cells (24), we examined the effect of our UV irradiation protocol on NER protein levels in human fibroblasts. Western blot analysis revealed no consistent modulations in the levels of ERCC3, PCNA, or XPA in fibroblasts up to 24 h after irradiation, regardless of donor age (Fig.…”
Section: During the Period Of Initial Repair (24 H) Uv Irradiation Dmentioning
confidence: 99%
“…Short-lived ubiquitous pauses would be poor substrates for UvrD-driven backtracking because of the existence of multiple anti-back-tracking mechanisms, while any significant delay in transcription elongation would serve as a trigger for UvrD-directed TCR. At the same time, it was reported that repair of cyclo-butane pyrimidine dimers does not depend upon transcription during SOS-response [66], which seemingly contradicts our model. However, the timing of the SOS-dependent induction could play a crucial role and explains the contradiction.…”
Section: When the Cells Yell "Sos"!contrasting
confidence: 93%
“…Insights & Perspectives ..... increases only twofold [66], which could be not high enough for efficient repair without TCR. In the same time UvrD is a plentiful protein even without SOS induction and a slight increase in UvrD concentration following SOS-activation at earlier stages can play an important role for cell survival via the dimerization mechanism described above.…”
Section: When the Cells Yell "Sos"!mentioning
confidence: 99%
“…Repeated exposure of E. coli to daily doses of X-ray or UV photons selects for highly resistant strains of the bacteria, able to withstand greater than 2 times the e¡ective UV dose required to inactivate the parent strain [10]. This e¡ect may be explained by the natural selection of certain individuals that contain high levels of DNA repair enzymes [11]. Mechsner et al [12] demonstrated that E. coli inactivated by low pressure UV repaired its DNA independent of photoreactivation, an e¡ect occurring after incubation of treated organisms in the dark for several days.…”
Section: Introductionmentioning
confidence: 99%